Pengaturan Tindak Pidana Pemerkosaan terhadap Sesama Jenis Kelamin Ditinjau dari Pasal 292 Kitab Undang-undang Hukum Pidana - Tia Nur Larasati; I Nyoman Gede Sugiartha; Diah Gayatri Sudibya (Jurnal Preferensi Hukum, 2021)
It can be said that the conviction of perpetrators of same-sex rape can be said to still contain obscure normsand that the Law of the Republic of Indonesia number 1 of 1946 concerning Criminal Law Regulations or the KUHP does not contain specific provisions that clearly regulate it. Article 292 of the Criminal Code is the only article of the Criminal Code that provides regulations regarding the crime of same sex rape. However, Article 292 of the Criminal Code only regulates the criminal act of same sex rape against minors as it can be categorized as an element of the crime of rape as stipulated in Article 285 of the Criminal Code, a criminal act of rape must be committed by men against women. The purpose of this study was to determine the criminal act of same sex rape according to Article 292 of the Criminal Code and to determine the legal sanctions against the perpetrator of the crime of same sex rape in Indonesia. The research method used is normative research, this type of normative research focuses on the collection and in-depth analysis of legal materials and also searches for their meaning in order to find solutions to the problem. Legal sanctions for perpetrators of the crime of rape of the same sex in Indonesia refer to the provisions of Article 292 of the Criminal Code, which is punishable by a maximum imprisonment of five years, as with the weight of the crime of a criminal act of rape whether committed against the opposite sex or of the same sex, punishment a maximum sentence of 5 (five) years is deemed not to contain a sense of justice, the formulation of criminal sanctions for rape in Articles 285 and 292 of the Criminal Code can be considered to be out of date or outdated.